The trader's pendulum : the 10 habits of highly successful traders - Samuels, Jody, 1957- (John Wiley & Sons, 2015)
The new trader's guide to the business, psychology, and hype in trading The Trader's Pendulum + Website is the ultimate toolkit for realizing your trading potential. Written by one of North America's leading trading coaches, this guide is designed to show aspiring traders how to design and implement a successful trading strategy by learning the psychological tricks behind solid trading philosophies. New and experienced traders alike will find value in The 10 Habits of Successful Traders, and come away equipped to navigate the real-life emotional-psychological effects of market chaos. You'll learn to embrace change and risk, and use it to your benefit as you climb out of the technical trap and stop riding the Trader's Pendulum between fear and greed. Based on the author's Elliott Wave and Harmonics expertise, this invaluable guide brings you a top-down approach to the market to help you maximize profit and minimize poor choices. The companion website gives you access to an interactive Trader's Scorecard, models for your 'business' and trading plan, The Trading Blotter, and a video synopsis of the all-important 10 habits. Today's global economy has forced people to search for a second cash flow stream to replace or supplement a primary income. It is more important than ever to have a reliable guide at your side, and this book gives you guidance and so much more.-Develop and follow a successful trading system -Make more money while saving time and effort -Treat trading like a business for lasting success -Use change and risk to your benefit Stop chasing trends and listening to widely disseminated bad advice. The Trader's Pendulum + Website is more than a guide-it's advice, examples, models, and more, giving you a practical roadmap to your online trading success.